2014
DOI: 10.1021/es500958b
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Effects of Aging and Weak Magnetic Fields on Sequestration of Selenite by Zero-Valent Iron

Abstract: The sequestration of Se(IV) by zero-valent iron (ZVI) is strongly influenced by the coupled effects of aging ZVI and the presence of a weak magnetic field (WMF). ZVI aged at pH 6.0 with MES as buffer between 6 and 60 h gave nearly constant rates of Se(IV) removal with WMF but with rate constants that are 10- to 100-fold greater than without. XANES analysis showed that applying WMF changes the mechanism of Se(IV) removal by ZVI aged for 6-60 h from adsorption followed by reduction to direct reduction. The stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
91
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 67 publications
14
91
0
2
Order By: Relevance
“…Our previous studies showed that the application of a weak magnetic field (WMF) could promote ZVI corrosion and significantly enhance Se(IV) removal by both pristine ZVI and aged ZVI [16,17], and greatly improve As(V) and As(III) removal by ZVI at pH ini 3.0-9.0 [18]. Liang et al [17] conducted numerical simulation to evaluate the flux density distribution near the ZVI sphere surface and revealed that the observed WMF effects arose from the ferromagnetism of ZVI and the paramagnetism of Fe 2+ . In the presence of a WMF, the magnetic field gradient force (F GMF ) tends to induce localized corrosion of the ZVI surface, which consequently accelerated ZVI corrosion and contaminants removal [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that the application of a weak magnetic field (WMF) could promote ZVI corrosion and significantly enhance Se(IV) removal by both pristine ZVI and aged ZVI [16,17], and greatly improve As(V) and As(III) removal by ZVI at pH ini 3.0-9.0 [18]. Liang et al [17] conducted numerical simulation to evaluate the flux density distribution near the ZVI sphere surface and revealed that the observed WMF effects arose from the ferromagnetism of ZVI and the paramagnetism of Fe 2+ . In the presence of a WMF, the magnetic field gradient force (F GMF ) tends to induce localized corrosion of the ZVI surface, which consequently accelerated ZVI corrosion and contaminants removal [17].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [17] conducted numerical simulation to evaluate the flux density distribution near the ZVI sphere surface and revealed that the observed WMF effects arose from the ferromagnetism of ZVI and the paramagnetism of Fe 2+ . In the presence of a WMF, the magnetic field gradient force (F GMF ) tends to induce localized corrosion of the ZVI surface, which consequently accelerated ZVI corrosion and contaminants removal [17]. However, no effort has been made to show that the positive effect of WMF on contaminants removal by ZVI corrosion was attributed to the enhanced mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Guan et al 19,22 developed ZVI premagnetization before the reaction to enhance the reactivity of ZVI toward various contaminants. However, the reactivity of premagnetized ZVI was not stable and decreased with time before the reaction.…”
Section: Effect Of Magnetization Timementioning
confidence: 99%
“…Recently, Guan et al 19,20 have done many comprehensive studies on weak magnetic eld (WMF) enhancing the removal of several heavy metals by microscale ZVI. The application of an inhomogeneous weak magnetic eld (WMF) (B max < 20 mT) could signicantly enhance Se(IV) removal by both pristine ZVI and aged ZVI 19,20 and greatly improve As(V) and As(III) removal by Fe 0 at pH ini 3.0-9.0.…”
mentioning
confidence: 99%
See 1 more Smart Citation